Yield-limiting nutrients for wheat (Triticum aestivum L.) production in Farta to Lay Gayint districts of the Amhara Region in Northwest Ethiopia - Asfaw, Abebe Getu; Gelagil, Demsew Bekele; Abebe, Getachew Yilma; Woldie, Wubayehu Gebremedhin; Getahun, Tesema Minale (Frontiers in Agronomy, 2025)
Wheat (Triticum aestivumL.) is the third most important crop in Ethiopia yet its productivity in the country remains significantly below experimental yields and water-limited yield potential due to soil fertility variability and the absence of site-specific fertilizer recommendations. To identify yield-limiting nutrients and support the development of a precision fertilizer recommendation tool, a nutrient omission study was conducted in the 2021 main cropping season across eight sites in the South Gondar Zone of Northwestern Ethiopia. The study evaluated eight treatments: (1) NF (NPKSZnB), (2) -B, (3) -Zn, (4) -S, (5) -K, (6) -P, (7) -N, and (8) F0, with nutrients applied at 138 kg N, 46 kg P2O5, 60 kg K2O, 10.5 kg S, 5 kg Zn, and 1 kg B ha-1. Results indicated that N omission significantly reduced wheat yield and yield-related traits across all sites, while P limitation was significant in 50% of the locations. The average yield response to N application was 2071.9 kg ha-1 (ranging from 847.2 to 2873.6 kg ha-1), followed by P, with a mean response of 499.1 kg ha-1 (16.6–850.8 kg ha-1). Soil indigenous nutrient supply (SINS) assessments revealed that N was only 45.0% sufficient, whereas P sufficiency was higher (87.0%). Potassium (K), sulfur (S), zinc (Zn), and boron (B) were found to be non-limiting, with soil supplies exceeding 90%. Yield gaps due to N and P omission averaged 53.9% and 11.9%, respectively, while omissions of K, S, Zn, and B had negligible effects. Agronomic efficiency was highest for P (22.2 kg kg-1), followed by N (13.1 kg kg-1) and K (5.2 kg kg-1). These findings demonstrate that N is the primary yield-limiting nutrient in the study area, with P being secondary in half of the evaluated farms. To enhance wheat productivity and minimize yield gaps, site-specific fertilizer recommendations emphasizing optimized N and P application are critical. The study was conducted for one season, and hence multi-year experiments to address season variation on the effect of the nutrient omission treatments is recommended.